2012
DOI: 10.1177/2047487312471759
|View full text |Cite
|
Sign up to set email alerts
|

Ability to sit and rise from the floor as a predictor of all-cause mortality

Abstract: Musculoskeletal fitness, as assessed by SRT, was a significant predictor of mortality in 51-80-year-old subjects. Application of a simple and safe assessment tool such as SRT, which is influenced by muscular strength and flexibility, in general health examinations could add relevant information regarding functional capabilities and outcomes in non-hospitalized adults.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
104
1
10

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 116 publications
(117 citation statements)
references
References 35 publications
2
104
1
10
Order By: Relevance
“…An interesting feature of this study is the use of the Flexitest, a dimensionless flexibility assessment protocol. Flexitest's intra-and interobserver reliabilities have been thoroughly evaluated (Araújo 2003), favorably contrasted with other methods used for joint range of motion assessment (Silva et al 2000), and it has been used in several research studies (Araújo 2008;Araújo and Araújo 2004;Araújo and Chaves 2005;Brito et al 2013Brito et al , 2012Chaves et al 2002;Coelho and Araújo 2000;Nobrega et al 2005;Signorelli et al 2012a, b;Silva et al 2000). Flexitest also presents several positive features, such as easiness by which mastering the measurement technique is achieved, standardization of no previous warming up routine, and the relatively short time for evaluation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An interesting feature of this study is the use of the Flexitest, a dimensionless flexibility assessment protocol. Flexitest's intra-and interobserver reliabilities have been thoroughly evaluated (Araújo 2003), favorably contrasted with other methods used for joint range of motion assessment (Silva et al 2000), and it has been used in several research studies (Araújo 2008;Araújo and Araújo 2004;Araújo and Chaves 2005;Brito et al 2013Brito et al , 2012Chaves et al 2002;Coelho and Araújo 2000;Nobrega et al 2005;Signorelli et al 2012a, b;Silva et al 2000). Flexitest also presents several positive features, such as easiness by which mastering the measurement technique is achieved, standardization of no previous warming up routine, and the relatively short time for evaluation.…”
Section: Discussionmentioning
confidence: 99%
“…Although, by reading their data, indeed, it can be identified that most studies are relatively short (few weeks long) and that flexibility was most often assessed by multicomposite tests, such as sit-andreach, which, in our opinion, may compromise the interpretation of the information. While it is widely recognized that to have some degree of range of motion in the major body joints is needed for performing most of the daily living activities, such as sitting and rising from the floor (Brito et al 2013), an ability that have been recently shown to be predictive of all-cause mortality in middle age and older adults (Brito et al 2012), it is still unknown what the ideal overall flexibility level for health is (Jackson et al 1998) or if there is a cutoff value for FLX regarding personal autonomy. There are some evidence that low levels of flexibility could be related to risk of falls in older adults, leading the authors to recommend that flexibility training be a priority for those subjects (Menz et al 2006;Dai et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…O envelhecimento aumenta o enfraquecimento muscular, caracterizada pela atrofia muscular das fibras tipo II, essa condição afeta a coordenação muscular, resultando em uma incapacidade funcional (Puthoff & Nielsen, 2007) e muitas vezes ocasionando a mortalidade (Brito, Ricardo, Araujo, Ramos, Myers, & Araujo, 2012).…”
Section: Discussionunclassified
“…Partindo do pressuposto de que a tarefa de sentar e levantar do chão são básicos para a autonomia do idoso, Brito et al (2012) realizaram estudo de coorte e identificaram que aqueles indivíduos com o menor escore no teste de sentar Figura 1. Área sob a curva ROC com o ponto de corte para o número de repetições no teste de sentar e levantar da cadeira como preditor para incapacidade funcional em homens idosos.…”
Section: Discussionunclassified
See 1 more Smart Citation